PERFORMANCE ANALYSIS OF OIL AND WATER PRODUCTION IN FIELD X USING DIAGNOSTIC PLOT - Rizki Nabila; Mohammad Wildan A; Ajeng Purna Putra Oktaviani Putra Oktaviani (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2021)
Production wells have to be evaluated periodically, one of the problems that can occur is early water problems. Using X-Plot, Chan’s Diagnostic Plot, Decline Curve Analysis and Hall Plot analysis be able to detect RN-01 and RN-02 wells experienced multilayer channeling and RN-03 experienced normal displacement with high WOR.